Early Hemodynamic and Sedative Effects of Perineural Dexmedetomidine Versus Dexamethasone in Supraclavicular Brachial Plexus Block - Dr. N. Lakshmi Sowmya; Dr.G Srinivasa Rao; Dr. P Mrunalini, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Perineural adjuvants are commonly added to local anaesthetics during supraclavicular brachial plexus block to improve block quality and prolong analgesia. While both dexmedetomidine and dexamethasone are effective, comparative data regarding their early hemodynamic and sedative effects remain limited. This study compared the early hemodynamic changes and sedation profiles of perineural dexmedetomidine and dexamethasone when used as adjuvants to ropivacaine. Methods: In this study, 80 ASA I–II patients aged 18–60 years undergoing elective upper-limb surgery under supraclavicular brachial plexus block received 30 mL of 0.5% ropivacaine with dexamethasone 8 mg, or dexmedetomidine 50 µg. Heart rate, systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), peripheral oxygen saturation (SpO₂), and Ramsay Sedation Score (RSS) were recorded from baseline to 45 minutes after block administration. Results: Baseline demographic and clinical characteristics were comparable between groups. The dexmedetomidine group demonstrated significantly lower SBP and DBP from 3 minutes onward (P<0.001) and lower heart rate at 15 and 30 minutes (P<0.001), although all values remained within physiological limits. MAP was significantly lower only at 45 minutes (P=0.006). Ramsay Sedation Scores were significantly higher in the dexmedetomidine group at 30 minutes (3.13±0.34 vs. 2.00±0.00; P<0.001) and 45 minutes (2.63±0.55 vs. 2.00±0.00; P<0.001), indicating cooperative sedation. Peripheral oxygen saturation remained above 98% in both groups throughout the study, with no episodes of respiratory depression, clinically significant hypotension, or bradycardia requiring intervention. Conclusion: Perineural dexmedetomidine provides superior conscious sedation with modest, clinically acceptable reductions in heart rate and blood pressure compared with dexamethasone, while maintaining excellent respiratory safety. It is a valuable adjuvant when mild intraoperative sedation and patient comfort are desired during supraclavicular brachial plexus block.